Chemical composition, antibacterial, antioxidant and insecticidal activities of moroccan Thapsia transtagana essential oil - Hakim ALILOU (Elsevier, 2021)
Introduction: The use of chemical products to neutralize microorganisms has always been a subject of discussion and research for alternative solutions, indeed, the use of essential oils has been a promising natural methodology. Methods: In our study we used the essential oils from different parts of Thapsia transtagana (Apiaceae), obtained by hydrodistillation, were identified and using Gas chromatography–mass spectrometry (GC–MS) and Gas Chromatography-Flame Ionization Detection (GC/FID) methods and evaluated against several bacteria of Gram- and Gram + bacteria. Disk diffusion, Minimum Inhibitory Concentration (MIC) and Minimum Microbicidal Concentration (MMC) methods have been used. Free radical-scavenging activity and insecticidal activity of Thapsia transtagana essential oils were also identified. Results: Majority products from different parts of Thapsia transtagana essential oil identified by GC–MS and GC/FID methods are 2,6-Dimethylnaphthalene, Pinane and Hexahydrofarnesyl acetone. The highest activity was found against Staphylococcus aureus using inflorescence essential oil with minimal inhibitory concentration value for 0,56 μg/μL. Insecticidal activity was also the subject of this study, roots and inflorescence essential oils demonstrated to have a remarkable potent against Acanthoscelides obtectus and Sitophilus oryzae using contact assessment, inhalation assessment and ingestion assessment tests. Insecticidal activity assay results showed a significant enhancement of mortality in both test insect pest on increasing the dose and exposure period. In the other hand, the different essential oils of Thapsia transtagana were evaluated for their radical scavenging activities by means of the 2,2-diphenyl-1-picryl-hydrazyl (DPPH) assay. The strongest scavenging activity was observed in inflorescences essential oil fraction scavenged radicals effectively at 100% using 500 mgL-1 concentration. Conclusion: Its essential oils were proved to have strong antimicrobial, insecticidal and antioxidant activities that allows it to be used by the pharmaceutical and cosmetic industries as natural preservative.